2016
DOI: 10.1094/pdis-07-15-0777-re
|View full text |Cite
|
Sign up to set email alerts
|

Pin Nematode Slow Decline of Anthurium andraeanum, a New Disease Caused by the Pin Nematode Paratylenchus shenzhenensis

Abstract: High population densities of the plant-parasitic nematode Paratylenchus shenzhenensis have been observed in association with stunted anthurium in Shenzhen, Guangdong Province, China. P. shenzhenensis is now recognized as a new pathogen that causes severe damage to anthurium. Commercial fields of anthurium infected by P. shenzhenensis present a patchy distribution of plants that are usually stunted and in decline and have yellowing leaves. Roots that are heavily infected by this nematode present brown, dark-bro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 12 publications
1
10
1
Order By: Relevance
“…We found that the main morphological characteristics of the LQ-1 population were basically consistent with H. microlobus as described previously, with only slight differences in some measurements. Compared with the data of Mwamula et al (2020), the L, b, c and max body diameter values for female nematodes were relatively smaller [22]; the pharynx length and m value of measurements were relatively larger. The reason for differences may be related to underlying genetic variation and geographical position.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…We found that the main morphological characteristics of the LQ-1 population were basically consistent with H. microlobus as described previously, with only slight differences in some measurements. Compared with the data of Mwamula et al (2020), the L, b, c and max body diameter values for female nematodes were relatively smaller [22]; the pharynx length and m value of measurements were relatively larger. The reason for differences may be related to underlying genetic variation and geographical position.…”
Section: Discussioncontrasting
confidence: 57%
“…1). The morphometric data from the LQ-1 population closely resembled H. microlobus as described previously [22] (Table 1).…”
Section: Morphology Of the Spiral Nematodessupporting
confidence: 65%
“…Wang, Xie, Li, Xu, Yu, and Wang [21] and P. projectus, cause varying degrees of damage to their hosts, including root injury and poor plant development, consequently decreasing yield and plant longevity [7,22].…”
Section: Of 25mentioning
confidence: 99%
“…Paratylenchus species are commonly known as pin nematodes. The short stylet species feed ecto-parasitically; however, some species feed endo-parasitically by gaining entry into lateral roots [5][6][7]. Pin nematodes are amongst the most frequently occurring PPN in Canada [8], and previous studies have reported the association of pin nematodes with forages, turf grasses, legumes, and cereal crops of Eastern and Central Canada [2,[9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…These species are distributed across different climatic zones and environments (Raski 1976;Esser 1992;Ghaderi et al 2014;Maria et al 2018a;Li et al, 2019). Some of the species were reported to be pathogenic and causing reduced root system and poor growth, notable examples are P. bukowinensis Micoletzky 1922 on parsley and celery (Brzeski 1975;Brzeski & Radzikowska 1980); G. epacris (Allen & Jensen 1950) Goodey, 1963 on walnut, G. capitatus (Adams & Eichenmuller 1962) Siddiqi & Goodey 1964 on oak, G. hamicaudatus (Cid del Prado Vera & Maggenti 1988) Brzeski, 1998 on redwood, P. projectus Jenkins 1956 on alfalfa (Webster et al 1967) and P. shenzhenensis Wang, Xie, Li, Xu, Yu & Wang 2013 on flamingo lily (Wang et al 2013).…”
Section: Introductionmentioning
confidence: 99%